Integration and Search Unemployment: An Analysis of Eastern EU Enlargement - Ben J. Heijdra; Christian Keuschnigg (Center for Economic Studies and ifo Institute (CESifo), 2000)
The paper develops a unified general equilibrium model including savings with overlapping generations, investment and search unemployment. Long-run analytical results for the small open economy identify capital accumulation as a prime transmission channel. The effects of integration on unemployment, however, depend importantly on the nature of wage taxation and unemployment compensation. As a separate methodological contribution, we extend a dynamic CGE model for Germany to allow for search unemployment of high- and low-skilled labour. Simulating the effects of Eastern EU enlargement, we find quantitatively small effects of integration but more pronounced labour market effects from immigration.
Keywords: 330; Finite lives; search unemployment; capital accumulation; trade; immigration